THE QUALITY OF ONLINE TEACHING AND LEARNING METHODS AS OFFERED BY LECTURERS DURING CORONAVIRUS-DISEASE-2019 AT THE UNIVERSITY OF LIMPOPO, SOUTH AFRICA - Rivoningo Nyiko Msisinyane; Prof Witness Maluleke; Karabo Malete (CV. RADJA PUBLIKA, 2024)
This study aims to assess the quality of online teaching and learning (T & L) methods offered by lecturers during Coronavirus Disease-2019 at the University of Limpopo (UL). A qualitative research approach and exploratory research design were employed. Non-probability purposive sampling was used to select participants. Data was collected using semi-structured Key Informant Interviews (KIIs), and inductive Thematic Content Analysis (TCA) was deployed to analyse the qualitative data. The literature review highlighted the challenges most rural or historically disadvantaged universities in South Africa faced in maintaining educational standards and equity in online learning. Moreover, the findings revealed significant issues, including compromised teaching quality, limited accessibility, inequality, and concerns about academic integrity. Despite these challenges, the university's initiatives, such as training, resource provision, plagiarism detection tools, and proctoring tools, helped mitigate some of these negative impacts. The study recommends continuous investment in digital infrastructure, regular updates to online platforms, and enhanced collaboration among faculties to support effective and equitable online T & L. These measures are crucial for sustaining high-quality education in the current digital environment.